Indonesian Student Entrepreneurial Intention in Cirebon: The Influence of Entrepreneurial Competence, Motivation, and Innovation - Hendarman, Fachrizal Ghiffari; Pujiastuti, Tri; Suzana, Anna (International Journal of Social Service and Research, 2025)
This study examines the influence of entrepreneurial competence, motivation, and innovation on the entrepreneurial intentions of students in Cirebon, Indonesia. Using a quantitative approach with a survey-based design, this study involved seventh-semester students from various universities in the region. The data were analyzed using multiple linear regression. The findings show that entrepreneurial competence, motivation, and innovation each have a statistically significant and positive effect on students’ entrepreneurial intentions, both individually and simultaneously. Among these factors, competence and innovation emerged as the most dominant predictors. In contrast, motivation shows a comparatively weaker impact when it is not supported by strong entrepreneurial skills and innovative thinking. These results underscore the importance of targeted educational interventions to strengthen entrepreneurial potential among students and support the development of a more innovation-driven entrepreneurial ecosystem in higher education. In addition, the study contributes to the growing literature on entrepreneurship in developing countries, highlighting how practical competence and creativity play a more decisive role than intrinsic drive alone. Higher education institutions are encouraged to integrate real-world entrepreneurship training and an innovation-based curriculum to better prepare students for the demands of modern entrepreneurship.